Edukasi dan Penanaman Tanaman Obat Keluarga (TOGA) sebagai Upaya Peningkatan Pengetahuan Masyarakat di Kelurahan Telaga Sam Sam Kecamatan - Yessi Rahayu; Amelia Rizka Rusanty; Athiyyah Al Aufi; Auliana Fikri Al Maula; Dinda Nur Syevita; Junita Putri Lestari; Rafles Rayhan Muharzaky; Rangga Febriadi; Sinta Intri Adha Riyana; Windra Meisya Putri; Yola Apriyani Dirma (Lembaga Pengembangan Kinerja Dosen, 2025)
Community Service Program (Kuliah Kerja Nyata/KKN) is a compulsory activity for university students as a form of community engagement and application of academic knowledge in real life. One of the work programs carried out was the education and cultivation of Family Medicinal Plants (Tanaman Obat Keluarga/TOGA), which aimed to improve the knowledge and practical skills of the community in Telaga Sam Sam Village, Kandis District, in cultivating and utilizing TOGA. Family medicinal plants have long been known to possess great potential as an alternative treatment for common illnesses such as fever, cough, stomachache, and skin itching, making them highly relevant to daily community health needs.The program was implemented through counseling sessions, interactive discussions, training, and hands-on practice of planting TOGA in the residents’ yards. The community actively participated in recognizing, cultivating, and maintaining various types of medicinal plants such as ginger, turmeric, galangal, lemongrass, and betel leaf. In addition to enhancing understanding, this activity encouraged households to practice simple herbal preparation techniques for family use.The results of the program showed a significant increase in community awareness regarding the importance of utilizing TOGA as a primary step in maintaining family health, while also contributing to the creation of a greener, cleaner, and healthier living environment. Furthermore, the activity not only improved community knowledge but also strengthened independence and self-reliance in utilizing local resources to support sustainable health practices.